Establishing multicultural society: Problems and issues of multicultural education in Indonesia - Cathrin, Shely; Wikandaru, Reno (Universitas Negeri Yogyakarta, 2023)
Creating a multicultural society that coexists peacefully amidst various kinds of differences is not an easy thing. The fact that multicultural society is still challenging to realize is a serious problem, not only for one or two countries but also for all countries worldwide. This research has three objectives. The first describes the implementation of multicultural education in Indonesia with various obstacles. Second, describe solutions to multiple problems in the implementation of multicultural education in Indonesia. Third, provide recommendations for the implementation of multicultural education in other areas. Based on a qualitative study of several studies on the implementation of multicultural education in Indonesia, The results show that the implementation of multicultural education in Indonesia is carried out in several ways or several approaches. In general, this approach can be divided into two: the approach in terms of learning materials and the approach in terms of learning methods. The multicultural education approach in terms of material means that the values of multiculturalism are given to students through special materials that discuss multiculturalism. Meanwhile, the approach in terms of methods means that the values of multicultural life are given to students by integrating them into various subjects namely the approach in terms of learning materials and approaches in terms of learning methods.